1982
DOI: 10.1042/cs0630555
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Renal Prostaglandin E Responsiveness in Decompensated Cirrhosis: Implications for Renal Sodium Handling

Abstract: 1. It has been suggested that endogenous renal prostaglandin E (PGE) constitutes a determinant of renal haemodynamics and renal sodium handling in patients with cirrhosis. We have accordingly assessed the effects of augmenting endogenous prostaglandins on renal function. We utilized water immersion to the neck since previous studies demonstrated that the redistribution of blood volume and concomitant central hypervolaemia thus induced produces a prompt and marked augmentation of PGE excretion in normal man. 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Epstein et al [41] have utilized water immersion to the neck, an experimental maneuver that redistributes blood volume with concomitant central hypervolemia and enhances PGE excretion in normal man. They demonstrated that decompensated cirrhotic patients manifested an increase in mean PGE excretion that was 3-fold greater than that observed in normal sub jects studied under identical conditions [46]. This was attended by a marked natriuresis and an increase in cre atinine clearance.…”
Section: Role O F Renat Prostaglandinsmentioning
confidence: 88%
“…Epstein et al [41] have utilized water immersion to the neck, an experimental maneuver that redistributes blood volume with concomitant central hypervolemia and enhances PGE excretion in normal man. They demonstrated that decompensated cirrhotic patients manifested an increase in mean PGE excretion that was 3-fold greater than that observed in normal sub jects studied under identical conditions [46]. This was attended by a marked natriuresis and an increase in cre atinine clearance.…”
Section: Role O F Renat Prostaglandinsmentioning
confidence: 88%
“…Although several neurohumoral alterations have been described in patients with well-established hepatic cirrhosis [3][4][5][6], it is possible that the physiopathological changes observed are not the same as those occurring in earlier stages of the disease. In fact, some results from cirrhotic patients [7] or from nonascitic cirrhotic rats [8] are not absolutely comparable to those previously de scribed.…”
Section: Introductionmentioning
confidence: 70%
“…The urinary excretion of PGE2 has been re ported to be increased in ascitic cirrhotic patients [11,12] and cirrhotic dogs [13] with normal renal function, and it has been proposed that PGE2 protects the renal function from the action of the different vasoconstrictor sub stances which appear to be increased in cirrhosis [5], However, normal urinary excretion of PGE2 has also been described in cirrhosis [7,8] and there is not enough information available about urinary PGE2 in early stages of the disease. Moreover, the fact that PGE2 synthesized by the different renal structures could have different physiological actions [9] has never been considered in hepatic cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Prostanoids formed in the liver control several functions of hepatocytes such as glycogenolysis [3] and DNA synthesis [4]. Hepatorenal syndrome and ascites retention, which are frequently recognized in cirrhotics, are also suggested to be related to prostanoid formation [5,6].…”
Section: Discussionmentioning
confidence: 99%